Characterization and antagonistic potentials of selected rhizosphere Trichoderma species against some Fusarium species - Olowe, Olumayowa Mary; Nicola, Lidia; Asemoloye, Micheal Dare; Akanmu, Akinlolu Olalekan; Sobowale, Ayodele Adegboyega; Babalola, Olubukola Oluranti (Frontiers in Microbiology, 2022)
Trichoderma fungi have been proved as efficient bioagents with great antifungal properties while many species in the plant’s rhizospheres have been characterized as plant growth-promoting agents. However, many rhizosphere Trichoderma are yet to be fully explored for plant disease management. In this study, Trichoderma species were isolated from the rhizosphere of maize, banana, and cassava, and their biocontrol potentials were screened against some Fusarium species from oak leaves (F2B and F3) and laboratory cultures (Fus 296 and Fus 294). The isolated rhizosphere Trichoderma were identified as Trichoderma virens 1 (TCIV), T. virens 2 (TCVII), T. virens 3 (TMSI), T. hazianum strain 1 (TCVI), T. harzianum strain 2 (TCVIII), T. erinaceum (TMZI), and T. koningiopsis (TMZII). The dual culture experiment recorded the highest percentage inhibition in TMZII against OakF2B (31.17%), TCVIII against Fus 294 (45.18%), TMZI against Fus 296 (47.37%), while TCIV was most effective against Oak F3 (44.15%). Among the Trichoderma culture filtrates evaluated, TCIV showed the highest percentage inhibition against Oak F3 (52.39%), Oak F2B (48.54%), Fus 294 (46.65%), and Fus 296 (44.48%). All the Trichoderma isolates demonstrated expressed varying levels of antagonism against the Fusarium pathogens in vitro.